(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Medication adherence is a critical factor in patient health management, especially for individuals with chronic diseases and elderly patients. Forgetting to take prescribed medication on time can lead to severe health complications. This research presents the design and development of an Arduino-based medication reminder system to assist patients in adhering to their medication schedules. The system utilizes a microcontroller (Arduino) integrated with an LCD display, a real-time clock (RTC) module, and a buzzer to alert patients at the correct dosage time. When the scheduled time arrives, the buzzer sounds, and the LCD displays the medication details, ensuring timely consumption. Additionally, the system can be enhanced with a mobile application or SMS alert for remote notifications. The proposed system is cost-effective, easy to use, and customizable for different medication schedules. Experimental results demonstrate its effectiveness in improving medication adherence. This solution has the potential to reduce hospital visits due to missed doses and improve overall patient health outcomes.